Studies on Ethology and Eco-physiology of the Antelopes of the Indian Desert - Bohra, H C; Goyal, S P; Ghosh, P K; Prakash, Ishwar (Annals of Arid Zone, 2016)
The present paper deals with the findings of a long term study conducted on the ethology and eco-physiologyof the antelopes, the chinkara or the Indian gazelle (Gazella benneui), the blackbuck (Antilope cervicapra) and the nilgai (Baselaphus tragocamelus) inhabiting the arid region of India. The blackbuck is basically a grazer and prefers open scrub lands, saline /lats or gravelly to hard pan soil having a waterhole nearby, whereas the chinkara is a browser and prefers sandy undulating or duny slopes or sandy to loamy bush lands and fallows. The presence of waterhole (s) in the chinkara habitat is desirable but is not essential. The chinkara’s preference for moisture laden leaves and flowers and its habit of seeking shade during the hottest part of the day curtails its dependence on free water intake. The nilgai’s preferred haunts are gravelly wasteland and piedmont areas as well as hard pan areas. Their numbers are considerably high around irrigated double cropped agricultural fields. The blackbuck and chinkara population are generally dwindling and hence they need protection whereas the nilgai has proved to be a menace to the standing crops as well as stored agricultural produce. The blackbuck and the chinkara may be further protected by demarcating some more areas around the Bishnoi dominated villages for preservation of the whole eco- system. These areas should be suitably fenced and should have assured feed and water supply which will keep the animals away from the crop fields. Special attention is required to be given to the problem of the fast multiplying nilgai population in the desert region. Uptil now, no viable method is available to keep the nilgaisaway from the crop fields.